Math, asked by sarthakrahate24, 1 year ago

Plz solve this question

Attachments:

Answers

Answered by india47
1

Step-by-step explanation:

3x-3+4x+4/x^2-1

7x+1/x^2-1=29/4x-1

by cross multiplying it we get

x^2+3x-28

by factorizing it we get

x^2-4x+7x-28

x(x-4)+7(x-4)

(x+7)(x-4)

x=-7,x=4

PLEASE MARK IT AS BRAINLIEST

Answered by sreedeviaddepal
0

Answer:

x=7,-4

Step-by-step explanation:

{[(3x-3+4x+4)]÷x^2-1} =29/4x-1

⇒(7x+1)(4x-1)=29x^2-29

⇒x^2-3x-28=0

(x-7)(x+4) =0⇒ x=7,-4

Similar questions